A stylistic analysis of Haji’s Book of Malayan Nursery Rhyme / Sabrina Adam - Sabrina, Adam (2017)
In the context of languages and linguistics, each individual possesses a distinctive style of language used despite sharing the same medium of language. This is because language and style are often interrelated and interwoven. The present study is aimed to identify the similarities and differences of stylistics features in both the source text and target text of the translated English nursery rhymes and to analyse which elements from the source text have been domesticated throughout the nursery rhymes translation process. Data for this research was collected from Hamilton’s Haji’s Book of Malayan Nursery Rhymes. In order to identify the similarities and differences of the stylistics features in both the English source text and Malay target text of the English nursery rhymes translated by Hamilton, a stylistic analysis was carried out and focused on (a) Lexico-Syntactic Patterns, (b) Lexico-Syntactic Choices and (c) Phonological Devices. The concept of domestication from Venuti’s foreignisation and domestication translation strategies was also analysed in order to explore Hamilton’s translation strategy in relating the English source language nursery rhymes to the target Malay language within specific linguistic and cultural constraints. Through the retention of the vital stylistics features in a translation process, the translator ensures that the literary devices which provide poetic or aestheticeffects from the source text is secured in the translation in order to offer the same entertaining and enjoyable learning experience. This is based on semantic and sound ambiguities which allow children to possess different learning skills that help them to focus on a specific idea, thought or sentiment by evoking and intensifying their understanding and emotional attachment to the nursery rhymes. Through the domestication translation strategy, it eases the local readers’ comprehension despite the cultural, educational and economic constraints and barriers which result in different social ideology. In addition, it encourages the local readers’ sense of familiarisation by conforming the translated nursery rhymes to the local Malayan cultural background and practice through the concept of relevancy and also to ensure its suitability as children nursery rhymes through more commonly used elements.